1999
DOI: 10.1084/jem.189.5.757
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Identification of a Mutated Human Melanoma Antigen Recognized by CD4+ T Cells

Abstract: CD4+ T cells play a critical role in generating and maintaining immune responses against pathogens and alloantigens, and evidence suggests an important role for them in antitumor immunity as well. Although major histocompatibility complex class II–restricted human CD4+ T cells with specific antitumor reactivities have been described, no standard method exists for cloning the recognized tumor-associated antigen (Ag). In this study, biochemical protein purification methods were used in conjunction with novel mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 166 publications
(100 citation statements)
references
References 36 publications
2
97
0
1
Order By: Relevance
“…Beside direct presentation of an Ag to T cells by tumor cells as previously suggested (33), cross-presentation of Ags by B cells or DCs has also been documented for the activation of both CD4 ϩ and CD8 ϩ effector cells (34). In previous studies, we noted that TIL1359 and TIL1087 cells can recognize 1359mel and 1087mel tumor cells respectively, but not autologous tumor lysates presented by EBV B cells (25,35), whereas TIL1363 and TIL1558 effector T cells recognize both whole tumor cells and tumor lysates presented by EBV B cells (27,28). In experiments to determine whether CD4 ϩ TIL164 Treg cells could recognize tumor cell lysates pulsed on B cells, we found that 164mel tumor cells expressing the ARTC1 ligand could specifically activate the corresponding CD4 ϩ Treg cells, but exogenous presentation of 164mel tumor cell lysate by the MHC class II-matched EBV-B cells lacked any stimulating effect on TIL164-C1 cells (Fig.…”
Section: Direct Presentation Of the Artc1 Peptide By Tumor Cells To Csupporting
confidence: 70%
See 1 more Smart Citation
“…Beside direct presentation of an Ag to T cells by tumor cells as previously suggested (33), cross-presentation of Ags by B cells or DCs has also been documented for the activation of both CD4 ϩ and CD8 ϩ effector cells (34). In previous studies, we noted that TIL1359 and TIL1087 cells can recognize 1359mel and 1087mel tumor cells respectively, but not autologous tumor lysates presented by EBV B cells (25,35), whereas TIL1363 and TIL1558 effector T cells recognize both whole tumor cells and tumor lysates presented by EBV B cells (27,28). In experiments to determine whether CD4 ϩ TIL164 Treg cells could recognize tumor cell lysates pulsed on B cells, we found that 164mel tumor cells expressing the ARTC1 ligand could specifically activate the corresponding CD4 ϩ Treg cells, but exogenous presentation of 164mel tumor cell lysate by the MHC class II-matched EBV-B cells lacked any stimulating effect on TIL164-C1 cells (Fig.…”
Section: Direct Presentation Of the Artc1 Peptide By Tumor Cells To Csupporting
confidence: 70%
“…Although all T cell clones secreted GM-CSF and IFN-␥ after exposure to target cells, TIL164-derived T cell clones secreted GM-CSF, IFN-␥, and IL-10, but no IL-2, IL-4, or TGF-␤. To compare with the cytokine profile of CD4 ϩ effector cell clones, we generated CD4 ϩ effector T cell clones from TIL1363 or TIL1558 cell lines (25,27,28). These T cell clones (TIL1363-C10, -C12, and TIL1558-C3, -C4) recognized the same corresponding target Ags/ peptides as the parental cell lines TIL1363 or TIL1558 (data not shown), and showed their ability to enhance the proliferation of naive CD4 ϩ T cells purified from fresh human PBMCs, as demonstrated in Fig.…”
Section: Establishment and Characterization Of Ag-specific Cd4 ϩ Tregmentioning
confidence: 99%
“…Of interest, although D7-pM CD4 ϩ T cells specifically reacted against intact DR1 ϩ MART-1 ϩ tumor cells, they failed to recognize DR1 ϩ EBV-B cells pulsed with lysates of MART-1 ϩ tumors. In the same experiment, CD4 ϩ TIL 1558 recognized processed 1558-mel lysate and provided a positive control for exogenous pathway processing (39). Thus, although MART-1 is a transmembrane protein, the pMART-1 epitope did not appear to be processed through the exogenous/endosomal route in these preliminary experiments.…”
Section: Resultsmentioning
confidence: 76%
“…3, D7-pM T cells recognized all of the 3 allogeneic melanomas tested that expressed both HLA-DR␤1 * 0101 and MART-1, but they failed to recognize DR1-negative or MART-1-negative cells. In the same experiment, DR1-restricted CD4 ϩ tumor infiltrating lymphocytes (TIL) 1558, specific for the TPImut antigen unique to 1558-mel, recognized 1558-mel but not the other tumors (39). Two repeat experiments yielded similar results.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation